Islamic Reform in Minangkabau: The Integration of Theology, Reason, and Science in the Thought of Abdul Karim Amrullah - Gazali, Gazali; Hadi, Rahmad Tri; Burhanuddin, Nunu; Ahmad, Ahmad (KALAM, 2025)
This article examines the dynamics of Islamic reform in Minangkabau through an analysis of the thought of Abdul Karim Amrullah, focusing on how he conceptualized the integration of theology, rationality, and scientific knowledge within his reformist project. While global scholarship on Islamic reform and the relationship between religion and science has largely focused on Middle Eastern thinkers, the intellectual contributions of Southeast Asian Muslim scholars remain relatively underexplored. Addressing this gap, the study investigates how Abdul Karim Amrullah articulated an epistemological framework that harmonizes revelation, reason, and science. The findings reveal that Abdul Karim Amrullah understood theology, rationality, and science as complementary rather than competing sources of knowledge. Grounded in the principle of tawḥīd, revelation functions as the ultimate normative authority, while reason operates as a divinely endowed faculty for interpreting both sacred texts and the natural world. Scientific inquiry, in this perspective, becomes a means of contemplating āyāt kawniyyah and strengthening religious consciousness. The study argues that Islamic reform in Minangkabau was not merely a movement of religious purification but also a project of epistemological reconstruction that sought to integrate theology, rational reasoning, and modern scientific knowledge. By situating Abdul Karim Amrullah’s thought within broader debates on Islam and science, the article highlights the contribution of Southeast Asian Islamic intellectual traditions to contemporary discussions on Islamic modernization.